Applications of stochastic semigroups to queueing models - Gwiżdż, Piotr (Annales Mathematicae Silesianae, 2018)
Non-markovian queueing systems can be extended to piecewisedeterministic Markov processes by appending supplementary variables to the system. Then their analysis leads to an infinite system of partial differential equations with an infinite number of variables and non-local boundary conditions. We show how one can study such systems by using the theory of stochastic semigroups.